Capability‐coordinated frequency control scheme of a virtual power plant with renewable energy sources. Issue 16 (24th July 2019) - Kim, Jinho; Muljadi, Eduard; Gevorgian, Vahan; Mohanpurkar, Manish; Luo, Yusheng; Hovsapian, Rob; Koritarov, Vladimir
Abstract : Growing trends in the deployment of inverter‐based renewable energy will decrease the inertia and frequency control capability of electric power systems by replacing conventional power plants; thus, the frequency of future power systems might be dynamic. This study proposes a capability‐coordinated frequency control (CCFC) scheme of a virtual power plant (VPP) including adjustable‐speed pumped storage hydropower (AS‐PSH), a wind power plant (WPP), and an energy storage system to support the frequency nadir and reduce the steady‐state error of system frequency. The CCFC scheme is based on a hierarchical‐control structure in which a CCFC organises the output of local frequency control units. To support the frequency nadir, the CCFC dispatches weighted frequency errors that are proportional to the available headroom of the units; thus, the errors are forwarded separately with a system frequency error to the primary control loop of each unit and thereby arrest the frequency nadir at a higher value than a system without the CCFC. To reduce the steady‐state error of the system frequency, the CCFC determines a partial active power command by additionally feeding an integrator of the CCFC with a modified frequency error that depends on the unit with the largest control.